How to design a house - Wilhide, Elizabeth (London ; Conran Octopus ; New York, NY Hachette Book Group USA, 2010)
"How to Design a House" tells you everything you need to know and looks at the principles and processes of designing a house, giving an insight into the design and building process. In a working case study John Pawson, one of the world's best-known architects, traces the design and development of his own house and reveals what it takes to create a successful blueprint
Keywords: Architect -- designed houses; Architecture -- Domestic; Dwellings -- Design and construction